The Motivations of Recreational Hunters Who Violate Wildlife and Game Hunting Regulations: Implications for Crime Prevention - Andrew Day; Stuart Ross; Jason Flesch; Simon J. Toop (Social Sciences)
Recreational hunting is a highly regulated activity, in part because it can give rise to a variety of deleterious social, environmental, and economic harms. It provides an interesting area for those interested in community safety because of the way in which both formal (e.g., enforcement officers, proscribed areas and times for hunting, licensing, etc.) and informal (e.g., community awareness and education, conservation) methods of crime prevention are applied. And yet, the criminological literature on effective regulation is not only limited but diverse in terms of scope, types of behavior considered (e.g., poaching, wildlife trading, recreation, etc.), and the context that is considered (e.g., geographical, cultural, etc.). In this paper, we present how a crime prevention and compliance response can be used to understand the nature of the issue and the individual and socio-political processes that result in non-compliance with hunting regulations. We present an overview of the status of recreational hunting in an Australian jurisdiction and locate the regulatory issues that arise within the research literature that explores the various motivations that are known to drive illegal hunting. These are then considered in relation to how community-oriented and non-coercive measures might be employed to improve prevent criminal behavior at the primary, secondary, and tertiary levels.